Management of Islamic Boarding Schools in the Implementation of Digital Da'wah Literacy Based on Religious Moderation and Gender Relations in West Java - Rustandi, Ridwan; Kusnawan, Aep (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This study aims to analyze the management of Islamic boarding schools in implementing digital da'wah literacy based on religious moderation and gender relations. The research explores digital competence in formulating digital da'wah formulations in educational institutions and da'wah Islamic boarding schools. The research was conducted in several West Java Islamic boarding schools, which have modern characteristics, have digital da'wah activities, and are affiliated with leading Islamic community organizations such as NU, Muhammadiyah, and Islamic Unity. The research was conducted with a qualitative approach. Research data were collected through observation, interviews, and documentation techniques. The results of the study show that the process of developing digital competence in Islamic boarding schools based on moderation and gender relations is carried out through habituation, improvisation, and innovation of the fundamental values of justice, equality, connectedness, relation, tolerance, moderation, wisdom, harmony, and inclusiveness as the foundation for strengthening digital competence. This is done through three stages. First, the stage of cultivating the students' values, knowledge, and skills is carried out through strengthening digital competence. Second, are the stages of fostering and assisting students in digital technology (digital usage). Third, the stages of controlling and supervising students in transforming digital technology (digital transformation) in a positive, innovative, emancipatory, and participatory manner.